KEANEKARAGAMAN SERANGGA PADA PERKEBUNAN KACANG PANJANG (Vigna sinensis) DI DESA MERITAI KECAMATAN RAMBUTAN KABUPATEN BANYUASIN SUMATERA SELATAN - Dewi Rosanti Dian Mutiara (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2013)
Research of  Insect Diversity on long bean (Vigna sinensis) in Meritai Village Rambutan Subdistrict   Sumatera Selatan Province, conducted  May till  Juni 2012, to saw species of long bean insect and its diversity. The research used direct survey method, and data sampling with purpossive in 6 transect and 4 subtransect in 50 m x 20 m areas.  The result showed gated 14 species long bean insects and diversity index was medium categhory with  H’ value  2,12. Key words :   diversity, insect,  Vigna sinensis